Effectiveness of Rational Emotive Behaviour Techniques on Cognitive Dimensions of Religious Intolerance Among Adolescents in Wukari Education Zone, Taraba State, Nigeria - Godswill Alhassan Moses; Ahmad Baba Muhammad (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The study examined the effectiveness of rational emotive behaviour techniques on cognitive dimensions of religious intolerance among adolescents in Taraba State, Nigeria. Two research hypotheses were formulated and tested at 0.05 level of significance. The population of this study was 1,514 SS1 students in Wukari Education Zone, Taraba State, Nigeria and a sample of 20 adolescents were drawn as subjects of the study using purposive sampling. The researchers used an adapted version of the Religious Intolerance Questionnaire (RIQ) with a reliability index of 0.78 for data collection. The data collected were analyzed using paired samples t-test to test hypothesis 1 and independent samples t-test to analyze hypothesis 2. The findings revealed that rational emotive behaviour techniques were effective in treating cognitive dimensions of religious intolerance. The findings also revealed that there was no gender difference in the effectiveness of rational emotive behaviour techniques on cognitive dimensions of religious intolerance. The study recommended among others that government and non-governmental organizations should train counsellors and psychologists in the effective utilization of rational emotive behaviour techniques in order to address cognitive distortions underlying religious intolerance.